ACCOUNTANTS ROLE CREATING COMPETITIVE NEW BRAND TRUCK FINANCE PRODUCTS FOR PT SM FINANCE INDONESIA - Yahya, Noel Krisnandar; Yuniarwati, Yuniarwati (Graduate Program of Universitas Tarumanagara, 2024)
This research aims to show the approach used and the active contribution of PT SM Pembayaran Indonesia (SMPI) Accountants in supporting the creation of new financing products in the new SMPI segment, namely Chinese brand Heavy Trucks which are starting to penetrate sales in Indonesia, so that new financing products are produced by the company can compete in the Indonesian market and industry, which of course will provide positive asset growth and increase profitability at SMPI. SMPI's profitability is the main thing, which aims to accelerate the rate of return on investments made by shareholders, which is also fundamental in investing in establishing SMPI. This research method used is a real case study at SMPI after SMPI saw a new opportunity that had not been exploited by similar financing companies, by conducting an in-depth study of the quality and reliability of the selected Chinese Heavy Truck brand as well as the Indonesian market's acceptance of the selected Chinese Heavy Truck brand. has been operating and demonstrated growing market share gains in existing markets in Indonesia. This includes how SMPI Accountants play an active role in leading the creation of new financing products in new segments to support additional positive growth in SMPI assets and contribute to increased SMPI profitability. The research results show that one of the Chinese Heavy Truck brands has good feasibility in terms of readiness to be accepted by the market in Indonesia and from the perspective of profitability projections for SMPI to work together in jointly marketing SMPI financing solutions with financing products intended for Chinese Heavy Truck brands in the commodity industry certain.